Control interno y su incidencia en el área administrativa y contable de la asociación de producción agropecuaria cacao aroma Asocaroma año 2022 - González Mendoza, Jesica Paola (2024)
The present study focuses on evaluating the impact of the accounting system on the operation of the administrative and financial areas of the Agropecuaria Cacao Aroma Production Association ASOCAROMA, located in the San Carlos parish of the Quevedo canton. Using data collected during the year 2022, we proceeded to verify the accuracy of transaction records, identify inadequate procedures applied in administrative and financial management, and conduct an analysis of financial indicators to support business decision-making using the COSO method. The methodology employed was based on visits to the association, the collection of documentation for information processing, and was complemented by interviews and surveys as research tools. The results showed that the correct implementation and compliance of the accounting system processes result in an increase in productivity, efficiency, efficacy and effectiveness of management throughout the work chain, from the production process to the top management, improving and facilitating the association's business management, specifically with regard to key decision making, and from the other end, improving the living and working conditions of the company's members through the correct marketing of the FAIRTRADE certificate.